Hetero aryl azo Disperse Dyes and Their Application on Polyester Fabric - Desai, B.K.; Dalal, M.M. (Asian Journal of Chemistry, 2010)
[2-Imine-(1'-hydroxy)-phenyl]benzothiazole (III) was prepared and coupled with different diazotized substituted aniline derivatives (Va-l) and their dyeing performance on polyester fabric was assessed. All the compounds (VIa-l) shows good substantivity for polyester fabric and gave bright yellow to brown shades with good to excellent light, wash, rubbing and sublimation fastness.